Neurohealth Properties of Hericium erinaceus Mycelia Enriched with Erinacines. (21st May 2018) - Li, I-Chen; Lee, Li-Ya; Tzeng, Tsai-Teng; Chen, Wan-Ping; Chen, Yen-Po; Shiao, Young-Ju; Chen, Chin-Chu
Abstract : Hericium erinaceus, an ideal culinary-medicinal mushroom, has become a well-established candidate in promoting positive brain and nerve health-related activities by inducing the nerve growth factor from its bioactive ingredient. Among its active compounds, only erinacine A has confirmed pharmacological actions in the central nervous system in rats. Hence, this review has summarized the available information on the neurohealth properties of H. erinaceus mycelia enriched with erinacines, which may contribute to further research on the therapeutic roles of these mycelia. The safety of this mushroom has also been discussed. Although it has been difficult to extrapolate the in vivo studies to clinical situations, preclinical studies have shown that there can be improvements in ischemic stroke, Parkinson's disease, Alzheimer's disease, and depression if H. erinaceus mycelia enriched with erinacines are included in daily meals.